Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1051/rnd:19830506
|View full text |Cite
|
Sign up to set email alerts
|

Estimation in vitro à l'aide du phosphore radioactif des besoins en phosphore des microorganismes du rumen

Abstract: Summary. In vitro estimate of rumen microbial requirements for phosphorus using 32 P label%d phosphate.Microbial requirements for P were assumed to be a function of the amount of microbial protein synthesis (microbial growth) and of the quantity of organic matter (OM) fermented in the rumen. The relationships among P incorporation into microbial matter and protein synthesis, ammonia utilization, volatile fatty acid (VFA) production and organic matter fermented (OMF) were studied in short-term incubations (3 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This change in fermentative activity was confirmed by significant reductions in cellulose and hemicellulose digestion with no apparent depression of starch digestion, indicating perhaps a change in the balance of the bacterial population (Latham et al 1974;Leedle & Hespell, 1984). Bryant et al (1959) have suggested a minimum requirement of 20 mg Pi/l for the maximum cellulolytic activity of pure cultures of cellulolytic bacteria, and extreme sensitivity of cellulolytic bacteria to P deficiency has been reported by Durand et al (1986). It has also been shown that cellulases isolated from mixed rumen bacteria associated with fibre have specific P requirements and that the enzymes show different affinities for different fibre fractions (Francis et af.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This change in fermentative activity was confirmed by significant reductions in cellulose and hemicellulose digestion with no apparent depression of starch digestion, indicating perhaps a change in the balance of the bacterial population (Latham et al 1974;Leedle & Hespell, 1984). Bryant et al (1959) have suggested a minimum requirement of 20 mg Pi/l for the maximum cellulolytic activity of pure cultures of cellulolytic bacteria, and extreme sensitivity of cellulolytic bacteria to P deficiency has been reported by Durand et al (1986). It has also been shown that cellulases isolated from mixed rumen bacteria associated with fibre have specific P requirements and that the enzymes show different affinities for different fibre fractions (Francis et af.…”
Section: Discussionmentioning
confidence: 86%
“…Other adaptive mechanisms contributing to P salvage in order to maintain nucleic acid synthesis have also been reported (Barsdate et al 1974). Reduced microbial-N flow at the duodenum of lambs and sheep receiving P-depleted diets has been reported (Breves et al 1985;Durand et al 19833) but the effect of P depletion on growth yield is uncertain, having been variously reported as having no or a reducing effect (Durand et al 1983b;Durand et al 1986). In the present work, although there was a reduction in microbial growth at low e concentrations, no evidence of reduced efficiency of microbial protein synthesis was observed at any level of 5.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pH of rumen fluid during P deficiency has been reported in vitro (Milton & Ternouth, 1984;Komisarczuk et al 1984) and in vivo (Holler, Breves & Martens, 1983). This may be explained by reduced VFA production as shown in vitro (Durand, Beaumatin & Dumay, 1983;Komisarczuk etal. 1984).…”
Section: Kinetics Of Rumen Fluid and Ammoniamentioning
confidence: 95%
“…Phosphorus content was important in T 4 and explains that the degradation of organic matter continues under its influence. In fact, phosphorus allows microorganism's longer life time than nitrogen (Durand et al 1983). The orthophosphate content from T 4 was higher than those obtained by Bokossa et al (2014a), whose maximum value was 2.80 mg/L.…”
Section: Effect Of Rabbit Manure On Nutrient Dynamics and Water Qualitymentioning
confidence: 76%